Beyond the lens of Courier Service industry: Understanding customer satisfaction and Loyalty among Young Consumers in Malaysia. - BELINDA KIM MOI, LIM (NONE, 2024)
This study delves into the courier service industry, concentrating on the satisfaction and loyalty of young consumers aged 18 to 35 years old in Malaysia. The primary aim was to examine the impact of Service Quality (SERVQUAL) dimensions on young consumers’ satisfaction. The SERVQUAL model, which includes aspects such as reliability, assurance and empathy, was found to significantly influence customer satisfaction. The study employed a quantitative approach, surveying 169 participants and analyzing the data using Smart PLS 4.0 software, ensuring robust and reliable findings. Another key objective was to explore the relationship between customer satisfaction and loyalty among young consumers. Results indicated a strong, positive correlation, suggesting that satisfied customers are more likely to remain loyal to a specific courier service. Additionally, the study investigated the moderating effect of perceived value on the satisfaction-loyalty relationship. However, this effect was found to be insignificant, implying that perceived value while important, does not significantly modify the satisfaction-loyalty dynamic in this context. This study offers valuable insights into the dynamics of customer satisfaction and loyalty in Malaysia’s courier service industry, highlighting the crucial role of service quality and perceived value in fostering customer loyalty. These findings provide actionable implications for industry practitioners and policymakers, supporting the growth and success of the courier service market in Malaysia. Ultimately, the study aims to enhance understanding, facilitate data driven decisions, and promote long-term customer loyalty in the industry. Keywords: Courier Service Industry, Young Consumers, Customer Satisfaction, Customer Loyalty, SERVQUAL.